Papéis dos profissionais da rede de apoio à inclusão escolar na educação infantil - Costa, Juliane Dayrle Vasconcelos da (2021)
Beyond the entry, it is also necessary to ensure the permanence, participation, and learning of students from the Target Public of Special Education (TPSE) in all levels, steps, and modalities of teaching. For this, the research recommends the offer of various types of support services, according to the potentialities, needs, and specificities of each person. The provision of various types of services demands a range of professionals, forming support networks for school inclusion, that acting in partnerships, with defined and clear roles, should seek common objectives, to ensure the necessary services to the schooling of the TPSE. The present study had as main objective, to describe and characterize a support network for school inclusion in children‟s education. As specific objectives pretended to: a) describe which professionals formed the support network for school inclusion in early childhood education and b) analyze the roles assigned and executed by these professionals who worked in child education with students TPSE. The study with qualitative approach, of descriptive type, had case study delineation, of a municipal network of a medium-sized city in the state of Pará. Thirty-two professionals participated in the study, including: one special education coordinator; four special education advisors; three professionals from the multiprofessional team; seven responsible for the management team; four common room teachers; three special education teachers and ten support professionals for school inclusion, acting in the municipal education network, in early childhood education, with TPSE children. The data collection instruments were: a characterization questionnaire; four semi-structured scripts of individual interviews and four semi-structured scripts of interviews with focus groups. The research design had three steps: ethical and initial referrals; knowing the locus, the professionals and the roles attributed to the professionals in the support network for school inclusion and finally, identification of the roles performed. After collection, the data were transcribed and reviewed, and then analyzed qualitatively, through thematic axes, titled with the names of the categories of the participating professionals. As end results, it was possible to identify the presence of different categories of professionals working in the support to students TPSE of the early childhood education of this municipality. However, having a significant number of actors does not mean that there is orchestrated performance and collaborative partnerships. In general, it is concluded that a clear definition of the roles of the professionals studied is necessary, as a strategy to reduce work overloads and deviations of functions.